Lafoeina tenuis G.O. Sars 1874 - Gravili, Cinzia; Vito, Doris De; Camillo, Cristina Gioia Di; Martell, Luis; Piraino, Stefano; Boero, Ferdinando (Zenodo, 2015)
Lafoeina tenuis G.O. Sars, 1874 Fig. 57 A, B See Cornelius (1995) for a complete synonymy. Material examined. HCUS-S 0 64 (Hydrozoa Collection, University of Salento—fauna of the Salento Peninsula). Description (based on our own observations; Cornelius 1995): Hydroid. Hydrorhiza as branched stolon system, usually anastomosed; colonies stolonal, minute, polymorphic with hydrothecae and nematothecae; hydrothecae tubular, narrower basally, sessile; operculum with about 10 triangular segments; nematothecae tubular, rounded distally, of variable length, aperture lateral and subdistal; gonothecae similar to hydrothecae. Gonophores as free medusae, described only within gonothecae. Cnidome. Basitrichous haplonemes. Habitat type. Eurybathic species found in the depth range 1–1060 m (Calder 1991; Calder & Vervoort 1998), typically epibiotic (Peña Cantero & García Carrascosa 2002; Cornelius 1995). Substrate. Other hydroids, algae, Posidonia , shells, bryozoans. Seasonality. January–May (C. Gravili unpublished observations); September–November (Boero & Fresi 1986); January (Galea 2007); April–May, August, November–December (Puce et al. 2009); September–May (De Vito 2006; this study). Reproductive period. Unknown in the Mediterranean Sea. Distribution. North Atlantic (eastern and western), Indian Ocean, Mediterranean (Kramp 1935; Millard & Bouillon 1973; Ramil 1988; Ramil & Vervoort 1992; Peña Cantero & García Carrascosa 2002 as Egmundella amirantensis Medel & López-González 1996; Bouillon et al. 2004; Galea 2007; Gravili et al. 2008a; Morri et al. 2009; Puce et al. 2009). Records in Salento. Rare at Otranto (De Vito 2006; Gravili 2006; Gravili et al. 2008a; this study). Remarks. The life cycle of L. tenuis is only imperfectly known (see Schuchert 2001a). Important discussions of L. tenuis are also found in Bouillon (1971), Calder (1991), and Cornelius (1995). References. Hadzi (1917, 1959), Stechow (1923), Broch (1933), Riedl (1959), Picard (1951a, 1958a), Rossi (1961), Repetto et al. (1977), ...